Efficient deadlock freedom checking using local analysis and SAT checking - Antonio, P; Gibson-Robinson, T; Roscoe, A (Springer, Cham, 2016)
We build upon established techniques of deadlock analysis by formulating a new sound but incomplete framework for deadlock freedom analysis that tackles some sources of imprecision of current incomplete techniques. Our new deadlock candidate criterion is based on constraints derived from the analysis of the state space of pairs of components. This new characterisation represents an improvement in the accuracy of current incomplete techniques; in particular, the so-called non-hereditary deadlock-free systems (i.e. deadlock-free systems that have a deadlocking subsystem), which are neglected by most incomplete techniques, are tackled by our framework. Furthermore, we demonstrate how SAT checkers can be used to efficiently implement our framework in a way that, typically, scales better than current techniques for deadlock analysis. This is demonstrated by a series of practical experiments.